Classical Electrodynamics and Green Functions with the Keller-Segel Equation - Nieto-Chaupis, Huber (2020)
Bacteria can transport a well defined electric charge so that one can expect electrical interactions with different biochemical compounds in order to optimize their colonization in healthy hosts. This paper focuses on the different manifestations of Keller-Segel equation from its reduced formulation and that is used to derive equations in a territory of classical electrodynamics. Therefore it was derived charge density and ionic current assumed to be created by the time variations while bacteria is carrying out inherent actions of chemotaxis. In addition, the correspondent Green's equation is derived.